A Genre-Based Analysis of Forward-Looking Statements in Corporate Social Responsibility Reports. (July 2019) - Yu, Danni; Bondi, Marina
Corporate social responsibility (CSR) reports are becoming a widespread corporate discourse practice and are often considered corporate image-building documents. The present study examines forward-looking statements in CSR reports from a genre-based perspective, aiming to better understand the textual practices of reporting genres in a globalized context and to raise awareness about ways they are used to shape perception of corporate activity. Using a corpus of 90 CSR reports in Chinese, English, and Italian and a subcorpus annotated with the "previewing future performance" move, the study combines a focus on genre-related contextual features and rhetorical patterns of CSR reports with a corpus-based study of future markers. The analysis reveals some cross-cultural variation in the distribution of the move, while its commissive function marks a common trend. Words indicating change ( miglior*/提升/improv* ) are found to be frequently used for future reference in all three languages, suggesting that future discourse, though regarded as an optional element of the genre, is widely exploited by companies in actual practice to promote a committed corporate image in CSR. Based on this analysis, the study puts forward the notion of "writing conformity, " a general feature of many reporting genres, which may turn out to pose new and important challenges for professional writers.